INSTRUMEN ADMINISTRASI DALAM PENEGAKAN HUKUM ATAS PELAKSANAAN IZIN LINGKUNGAN - Desita Andini; Risno Mina (Jurnal Yustisiabel, 2020)
This study aims to examine administrative instruments in environmental law enforcement, environmental implementation and sanctions against environmental law enforcement administration for environmental implementation. The research method used is normative legal research. Administrative instruments for law enforcement of environmental implementation are carried out in the form of supervision, enforcement of administrative sanctions, and lawsuit on State Administration. The use of administrative environment law enforcement instruments is carried out by government agencies as well as by the public or civil legal entities. Administrative sanctions instruments used in the context of environmental law enforcement administration. Administrative orders for environmental law enforcement in environmental permits are written warning, government coercion, environmental permits, and revocation of environmental permits.